Implications Of Human Resource Analytics On Employee Performance In Pharma Industry In South India-A Literary Study (International Journal of Innovative Research in Engineering & Management, 2022)
Human resource activities extend beyond  hiring and orientation. With the advent of HR analytics,  the human capital industry has seen a profound  transformation. Employer turnover analysis, talent supply  chain optimization, decision-maker insight extraction, and  other tasks are all accomplished by organisations using  HR analytics.
Keywords: Human Resource; Analytics; Employee; Performance; South Indian; Pharmaceutical; Industry